The Comparison of the Effects of Practice Schedules on Generalized Motor Program and Parameter Timing Transfer and Learning - Alireza Saberi; Hosien Samadi; Alireza Farsi; Korosh Ghahraman; Hamid Sedaghat (رشد و یادگیری حرکتی ورزشی, 2010)
This research was performed to monitor the effects of different practice schedules on learning and transfer of generalized motor program and timing parameter in a serial task. For this purpose, 80 participants (age: 19-23 years) voluntarily participated in this research and then they were divided randomly into 4 groups: blocked, random, blocked-random and random-blocked. This test included performance of serial tasks with different generalized motor programs (spatial dimension variance) and variable timing parameter. The participants accomplished 108 trials (pretest) and participated in retention and transfer tests. After these tests, the amount of relative timing error (measure of consistency and proficiency of generalized motor program) and absolute timing error (measure of accuracy and proficiency of parameterization) was calculated. Analysis of variance and post hoc Tukey test were used to analyze the data. The results showed a significant difference (P?0.05) among practice schedules in the acquisition phase, but in transfer and retention phases, despite the relative priority of combined practice groups, there was no significant difference among the groups.